2010
DOI: 10.1088/0004-6256/139/5/1871
|View full text |Cite
|
Sign up to set email alerts
|

The Kinematics of the Globular Cluster System of NGC 5128 With a New Large Sample of Radial Velocity Measurements

Abstract: New radial velocity measurements for previously known and newly confirmed globular clusters in the nearby massive galaxy NGC 5128 are presented. We have obtained spectroscopy from LDSS-2/Magellan, VIMOS/VLT, and Hydra/CTIO from which we have measured the radial velocities of 218 known, and identified 155 new, globular clusters. The current sample of confirmed globular clusters in NGC 5128 is now 605 with 564 of these having radial velocity measurements, the second largest kinematic database for any galaxy. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 152 publications
(181 reference statements)
7
119
0
1
Order By: Relevance
“…The measured line splitting is 280 km s −1 (Table 12), and both components are narrow, with the redder component the stronger one. The redder component is within 40 km s −1 of the radial velocity of the GC (649 km s −1 , Woodley et al 2010a), and this was confirmed in the FLAMES spectra by measuring the velocity of the GC Hβ absorption line (see Sect. 5.3).…”
Section: Double Line Pnesupporting
confidence: 53%
See 2 more Smart Citations
“…The measured line splitting is 280 km s −1 (Table 12), and both components are narrow, with the redder component the stronger one. The redder component is within 40 km s −1 of the radial velocity of the GC (649 km s −1 , Woodley et al 2010a), and this was confirmed in the FLAMES spectra by measuring the velocity of the GC Hβ absorption line (see Sect. 5.3).…”
Section: Double Line Pnesupporting
confidence: 53%
“…The radial velocity of this GC was measured by Woodley et al (2007) as 689 ± 16 km s −1 and so was taken as the template velocity. Cross correlating the other GC spectra against this template, and comparing the measured velocities with those from Woodley et al (2007Woodley et al ( , 2010a for 17 GCs enabled a modified template velocity to be determined which better matched, on average, the velocities from the literature, and resulted also in consistent velocity for HGHH-C4 within the error. All cross-correlation measurements were preformed using the IRAF fxcor task.…”
Section: Pne In Globular Clustersmentioning
confidence: 94%
See 1 more Smart Citation
“…The amount of HI associated with the central dust lane is 3.5 × 10 8 M , and there is about the same amount of H 2 (Charmandaris et al 2000). At < ∼ 10 9 M (Charmandaris et al 2000), the total gas mass is much less than the total dynamically determined mass of the galaxy of (1.3 ± 0.5) × 10 12 M within a galactocentric radius of 45 kpc (Woodley 2006;Woodley et al 2007Woodley et al , 2010a, equivalent to a total stellar mass ∼10 11 M .…”
Section: Introductionmentioning
confidence: 99%
“…Globular clusters (Puzia et al 2004;Bergond et al 2006;Romanowsky et al 2009;Shen & Gebhardt 2010;Schuberth 2010;Woodley et al 2010) or planetary nebulae (PNe, see, e.g. Napolitano et al 2001Napolitano et al , 2002Mendez et al 2001;Peng et al 2004;Douglas et al 2007;Coccato et al 2009;Teodorescu et al 2010;Napolitano et al 2011) have made it possible to extend kinematics up to 5−7 R eff , from the ≈R eff achievable with only stellar observations.…”
Section: Preliminariesmentioning
confidence: 99%